Needs Analysis of Interactive Multimedia Development for Teaching Number Patterns in Fifth Grade Elementary School - Amelia, Tasya Faricha; Hiltrimartin, Cecil; Somakim, Somakim (Program Magister Teknologi Pendidikan Universitas Jambi, 2026)
Despite the growing use of interactive multimedia and game-based learning in mathematics education, educational escape room games specifically designed for teaching number patterns in elementary schools remain limited and are rarely developed based on comprehensive needs analyses. This study aimed to analyze the need for developing interactive multimedia in the form of an educational escape room game for fifth-grade elementary school students. A descriptive quantitative survey was conducted involving 55 fifth-grade students and 10 teachers at SD Negeri 19 Talang Kelapa. Data were collected using validated Likert-scale questionnaires covering four aspects: teacher needs, student characteristics, learning media, and instructional design. The findings revealed that teacher needs were categorized as needed (73.2%), student characteristics as highly needed (82.4%), learning media as highly needed (87.1%), and instructional design as needed (61.7%). The learning media aspect showed the highest level of need, indicating the importance of engaging, interactive, and accessible digital resources to support mathematics learning. The proposed innovation emerging from this study is the integration of educational escape room game elements into interactive multimedia for number pattern instruction. These findings provide empirical evidence and practical guidance for developing interactive multimedia that aligns with students’ learning characteristics, teachers’ instructional needs, and effective instructional design principles. Future research is recommended to develop, implement, and evaluate the effectiveness of the proposed multimedia in improving students’ mathematical understanding and problem-solving skills.